(NpRIRODOOHRANNAQ TEHNOLOGIQ ZA]ITY RASTENIJ (B/s - (NwASILXEW(B, (NwADIM pETROWI^s; (NgORALX(B, (NwIKTOR mARTYNOWI^s; (NlESOWOJ(B, (NmIHAIL pAWLOWI^s ((NkIEW (B:s (NuROVAJ(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 165-166 (31 (NNAZW(B.)s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NzA]ITA RASTENIJ (B- (Nussrs